2016
DOI: 10.1021/acsami.6b05640
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimension Hierarchical Al2O3 Nanosheets Wrapped LiMn2O4 with Enhanced Cycling Stability as Cathode Material for Lithium Ion Batteries

Abstract: A three dimensional (3D) Al2O3 coating layer was synthesized by a facile approach including stripping and in situ self-assembly of γ-AlOOH. The uniform flower-like Al2O3 nanosheets with high specific area largely sequesters acidic species produced by side reaction between electrode and electrolyte. The inner coating layer wrapping spinel LiMn2O4 effectively inhibits the dissolution of Mn by suppressing directive contact with electrolyte to enhance cycling stability. The rate performance is improved because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 47 publications
4
29
0
Order By: Relevance
“…Especially, the octahedral LiMn 1.95 Mg 0.05 O 4 sample can exhibit a higher capacity of 91.8 mAh g −1 at a high cycling rate of 5.0 C. To further explore the high-rate cycling stability, the octahedral LiMn 1.95 Mg 0.05 O 4 samples were cycled at 10 C. The corresponding characteristic discharge curves are shown in Figure 6a. It can be found that the characteristic voltage plateaus in the discharge curves become blurred to a large extent, which agrees with the research result [39,44,45]. Figure 6b presents the cycling performance of the octahedral LiMn 1.95 Mg 0.05 O 4 samples at 10 C. It can show satisfactory retention of 97.5% after 100 cycles with initial capacity of 72.1 mAh g −1 .…”
Section: Resultssupporting
confidence: 86%
“…Especially, the octahedral LiMn 1.95 Mg 0.05 O 4 sample can exhibit a higher capacity of 91.8 mAh g −1 at a high cycling rate of 5.0 C. To further explore the high-rate cycling stability, the octahedral LiMn 1.95 Mg 0.05 O 4 samples were cycled at 10 C. The corresponding characteristic discharge curves are shown in Figure 6a. It can be found that the characteristic voltage plateaus in the discharge curves become blurred to a large extent, which agrees with the research result [39,44,45]. Figure 6b presents the cycling performance of the octahedral LiMn 1.95 Mg 0.05 O 4 samples at 10 C. It can show satisfactory retention of 97.5% after 100 cycles with initial capacity of 72.1 mAh g −1 .…”
Section: Resultssupporting
confidence: 86%
“…This blue shift may be contributed to the fact that a little amount of vanadium ions penetrates into the spinel structure on the surface lattice, shortening the average bond length of Mn-O. 50,56 This results to the strengthen of surface stability of the spinel structure, which agreed well with the results obtained from XRD. Additionally, the similar observation from FTIR spectra was also reported for VO x -coated LiMn 2 O 4 spinel nanorod clusters.…”
Section: Physical Characterization Propertiessupporting
confidence: 86%
“…Coating materials are divided into the following three categories: (1) transition metal oxides, (2) conductive materials, and (3) other active materials. Transition metal oxides, including Al 2 O 3 [7][8][9], ZnO [10,11], SiO 2 [12,13], and TiO 2 [14], act as a physical protection layer on the particle surface of LMOs to prevent or suppress chemical reactions with electrolytes. The cyclability of LMOs at high temperatures is improved by deposition of chemically stable materials, while electrochemically inactive features of oxides exhibiting low ion and electron conductivities lead to a loss of rate or power capabilities [15].…”
Section: Introductionmentioning
confidence: 99%